Urban tourism planning for sustainability - A literature review (Research, Society and Development, 2020)
In the context of globalization, the competitiveness of the tourist destination is increasingly a foundation of economies that depend directly on this activity (Garau-Taberner, 2007). Tourist destinations must implement processes of action, where the competitive strategy (Ferreras, 2010) is a reality. The emergence of tourist facilities and services contribute to a new urban identity, characterizing urban tourism. The aim of this theoretical essay is to present a brief theoretical framework, through a critical analysis of the literature, that justifies the possibility of relating the concepts of tourism, tourism, urban tourism demand, planning - as a process towards sustainability - and the use of technologies - as a factor that influences the growth of local accommodations - current trends in the tourism sector. The results prove that competitiveness can be seen as the ability to efficiently generate, process and apply knowledge in a global network of interaction, aiming at productivity, local competitiveness (Castells, 2000) and sustainable planning (Costa, 2003). However, despite the existence of a global environment, competitiveness is a potentially localized process (Porter, 1989). Faced with this ambiguity, territory emerges as a determining factor for the sector's competitiveness (Buhalis, 2000; Ritchie & Crouch, 2003).